Aedes Albopictus and Cache Valley virus: a new threat for virus transmission in New York State. Issue 1 (31st December 2022) - Dieme, Constentin; Maffei, Joseph G.; Diarra, Maryam; Koetzner, Cheri A.; Kuo, Lili; Ngo, Kiet A.; Dupuis II, Alan P.; Zink, Steven D.; Backenson, P. Bryon; Kramer, Laura D.; Ciota, Alexander T.
ABSTRACT: We report surveillance results of Cache Valley virus (CVV; Peribunyaviridae, Orthobunyavirus ) from 2017 to 2020 in New York State (NYS). Infection rates were calculated using the maximum likelihood estimation (MLE) method by year, region, and mosquito species. The highest infection rates were identified among Anopheles spp. mosquitoes and we detected the virus in Aedes albopictus for the first time in NYS. Based on our previous Anopheles quadrimaculatus vector competence results for nine CVV strains, we selected among them three stains for further characterization. These include two CVV reassortants (PA and 15041084) and one CVV lineage 2 strain (Hu-2011). We analyzed full genomes, compared in vitro growth kinetics and assessed vector competence of Aedes albopictus . Sequence analysis of the two reassortant strains (PA and 15041084) revealed 0.3%, 0.4%, and 0.3% divergence; and 1, 10, and 6 amino acid differences for the S, M, and L segments, respectively. We additionally found that the PA strain was attenuated in vertebrate (Vero) and mosquito (C6/36) cell culture. Furthemore, Ae. albopictus mosquitoes are competent vectors for CVV Hu-2011 (16.7–62.1% transmission rates) and CVV 15041084 (27.3–48.0% transmission rates), but not for the human reassortant (PA) isolate, which did not disseminate from the mosquito midgut. Together, our results demonstrate significant phenotypic variability among strains and highlight the capacity for Ae. albopictus to act as a vector of CVV.